cho \(a.b=m^2\)
\(a+b=2\left(m-1\right)\)
biết \(\left(a-b\right)^2+6m=a-2b\)
tìm \(m\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^3+3x^2+\frac{2x}{x^4}+x\)
\(=x\left(x^2+3x+\frac{2}{x^4}+1\right)\)
a, \(\left(x-1\right)^2+x\left(5-x\right)=8\Leftrightarrow x^2-2x+1+5x-x^2=8\)
\(\Leftrightarrow3x+1=8\Leftrightarrow x=\frac{7}{3}\)
b, \(\left(12x^4-6x\right):6x+2x\left(2+x\right)\left(2-x\right)=7\)
Ta có : \(\left(12x^4-6x\right):6x=2x^3-1\)
\(\Leftrightarrow2x^3-1+2x\left(4-x^2\right)=7\)
\(\Leftrightarrow2x^3-1+8x-2x^3=7\Leftrightarrow x=1\)
a, \(A=x\left(x+4\right)-6\left(x-1\right)\left(x+1\right)+\left(2x-1\right)^2\)
\(=x^2+4x-6\left(x^2-1\right)+4x^2-4x+1\)
\(=x^2+4x-6x^2+6+4x^2-4x+1=7\)
b, Ko hiểu đề bài
\(A=\left(x+3\right)^2+\left(x-2\right)^2-2\left(x+3\right)\left(x-2\right)=\left(x+3-x+2\right)^2=5^2=25\)
\(A=\left(x+3\right)^2+\left(x-2\right)^2-2\left(x+3\right)\left(x-2\right)\)
\(=\left[\left(x+3\right)-\left(x-2\right)\right]^2\)
\(=\left(x+3-x+2\right)^2\)
\(=5^2\)
\(=25\)